1985
DOI: 10.1093/oxfordjournals.eurheartj.a061851
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of nonclinical ventricular tachycardia induced in amiodarone-treated patients

Abstract: The clinical significance of sustained nonclinical ventricular tachycardia (VT) induced during electrophysiologic studies was studied in 10 amiodarone-treated patients. Nine patients had previous myocardial infarction while 1 patient had right ventricular dysplasia. All patients had only a single morphologic type of VT recorded during the multiple spontaneous episodes of tachycardia. After serial pharmacological electrophysiologic testing, the patients were placed on antiarrhythmic regimens which included amio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…We also found that laboratory induction of sustained nonclinical VT in amiodarone-treated patients does not imply the likelihood of their future spontaneous occurrence and therefore their prevention may not be required. 111 Finally, we extensively reviewed the noninvasive and invasive strategies for the prevention of sudden death after myocardial infarction. 112 , 113 …”
Section: Pvs and Risk Stratificationmentioning
confidence: 99%
“…We also found that laboratory induction of sustained nonclinical VT in amiodarone-treated patients does not imply the likelihood of their future spontaneous occurrence and therefore their prevention may not be required. 111 Finally, we extensively reviewed the noninvasive and invasive strategies for the prevention of sudden death after myocardial infarction. 112 , 113 …”
Section: Pvs and Risk Stratificationmentioning
confidence: 99%